Does CEO tenure moderate the link between corporate social responsibility and business performance in small- and medium-sized enterprises? - Lee, Sae-Mi; Sinha, Paresha N.; Bae, Jee-Eun; Lee, Yong-Ki (Frontiers in Psychology, 2022)
This study investigates the effect of CSR activities on business performance of small and medium-sized enterprises (SMEs) in South Korea setting. Based on upper echelons theory and stakeholder theory, the study further examines CEO tenure as a potential moderator between CSR activities and business performance. The study considers four dimensions of CSR (economic, legal, ethical, and philanthropic) and two types of business performance (financial and non-financial). To test the moderating effect of CEO tenure, we divided the sample into two groups: companies with short-term tenured CEOs and long-term tenured CEOs. The data were collected from 443 CEOs of SMEs in South Korea. We used a multi-group analysis with SmartPLS 4. The study finds that CEO tenure moderates the relationship between dimensions of CSR and business performance. More specifically, the study finds that CEOs in early-stage tenure focus on philanthropic activities to drive financial performance, while their counterparts focus on economic/legal dimension. CEOs, regardless of the length of tenure, consider the philanthropic dimension helpful for improving both financial and non-financial performance. This study expands prior research by examining the relationship between CSR and business performance in SMEs, considering the impact of the CEO tenure. The findings of this study make contributions to the literature by demonstrating that CEO tenure is an important factor in linking CSR to business performance. This research also adds evidence to the CSR literature that economic and legal dimensions are considered mandatory responsibilities, and CEOs of SMEs view them as interconnected. For practical implications, this study identifies different predictors of financial performance for companies with short-term vs. long-term CEO tenure. Short-term CEOs focus on philanthropy to improve financial performance, and both long and short-term CEOs believe that philanthropy affects the company's financial and non-financial performance.